Effect of Glacial/Interglacial Recharge Conditions on Flow of Meteoric Water Through Deep Orogenic Faults: Insights Into the Geothermal System at Grimsel Pass, Switzerland. Issue 7 (7th July 2021) - Alt‐Epping, Peter; Diamond, Larryn W.; Wanner, Christoph; Hammond, Glenn E.
Abstract: Many meteoric‐recharged, fault‐hosted geothermal systems in amagmatic orogenic belts have been active through the Pleistocene glacial/interglacial climate fluctuations. The effects of climate‐induced recharge variations on fluid flow patterns and residence times of the thermal waters are complex and may influence how the geothermal and mineralization potential of the systems are evaluated. We report systematic thermal‐hydraulic simulations designed to reveal the effects of recharge variations, using a model patterned on the orogenic geothermal system at Grimsel Pass in the Swiss Alps. Previous studies have shown that fault‐bounded circulation of meteoric water is driven to depths of ∼10 km by the high alpine topography. Simulations suggest that the current single‐pass flow is typical of interglacial periods, during which (a) meteoric recharge into the fault is high (above tens of centimeters per year), (b) conditions are at or somewhat below the critical Rayleigh number, and (c) hydraulic connectivity along the fault plane is extensive (an extent of at least 10 km into increasingly higher terrain is required to explain the 10 km penetration depth). The subcritical condition constrains the bulk fault permeability to <1e‐14 m 2 . In contrast, the limited recharge during the numerous Pleistocene glaciation events likely induced a layered flow system, with single‐pass flow confined to shallow depths while non‐Rayleigh convection occurred deeper in the fault. The same layering can be observed at low aspect ratios (length/depth) of the fault plane, when the available recharge area limits flux through the fault. Plain Language Summary: Many fault‐hosted geothermal systems in mountainous regions have been active through the Pleistocene glacial/interglacial climate fluctuations. As a result of climate change, meteoric recharge into these systems has changed over time, affecting geothermal circulation in the fault and hence influencing the geothermal and mineralization potential of the systems. We present a series thermal‐hydraulic simulations designed to reveal the effects of recharge variations, using a model patterned on the orogenic geothermal system at Grimsel Pass in the Swiss Alps. Previous studies have shown that fault‐bounded circulation of meteoric water is driven to depths of ∼10 km by the high alpine topography. Simulations suggest that the current single‐pass flow pattern is typical of interglacial periods, during which (a) meteoric recharge into the fault is high, (b) the contribution of buoyancy as a driving force for fluid flow is low, and (c) hydraulic connectivity along the fault plane is extensive. The deep, single‐pass flow pattern constrains the bulk fault permeability to <1e‐14 m 2 . In contrast, the limited recharge during the numerous Pleistocene glaciation events likely induced a layered flow system, with single‐pass flow confined to shallow depths while slow non‐Rayleigh convection occurred deeper in the fault. Key Points: Gradients in topography can drive meteoric water to depths exceeding 10 km where it acquires temperatures in excess of 250°C Recharge limited conditions induce a layered flow system in orogenic faults with shallow single pass flow and deep non‐Rayleigh convection If the depth of meteoric infiltration is known, a minimum length of the fault plane can be estimated